Malaysian financial well-being during COVID-19 pandemic: does income classification make a difference? - Che Norhalila Che Mohamed; Nur Izzati Ahmad Nasharuddin; Nur Aishah Mohamed Yussof; Nora Mohd Basir (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Covid-19 pandemic has affected emotions, health, and the community's well-being. It is even worse when the movement control order had to be carried out to curb the spread of this epidemic, which indirectly affected the financial well-being of individuals in Malaysia. Every person in society is affected by their income source for various reasons. Job losses, and a lack of adequate savings and emergency funds, accompanied by debt and loan management, will exacerbate the situation. An individual's or household's health and financial stability are important aspects of financial well-being for living a better daily life. It encompasses more than just a person's financial situation; it also includes their ability to meet financial goals and obligations, as well as their level of financial stress. As a result, this study aims to compare the financial well-being of Malaysian individuals between income classifications (B40, M40, and T20). Convenience sampling was used to get 265 respondents by using an online survey. A Kruskal Wallis test showed a statistically significant difference in financial well-being between income classifications, χ2 = 13.818, p-value = 0.001. Financial well-being for B40 is the lowest, followed by M40 and T20. The implications of acute financial well-being will lead inability to meet basic needs such as housing, food, healthcare, and education. Employees were recommended to have retirement savings and an excellent financial attitude to have good financial well-being.